Measuring for nonsynostotic head deformities in preterm infants during NICU management: A pilot study. (April 2019) - Willis, Sarah; Hsiao, Robert; Holland, Ruth A.; Lee, Kelly; Pitetti, Ken
Abstract: Background: Research has focused on the presence of nonsynostotic head deformities (NHD: plagiocephaly, dolichocephaly, brachycephaly) in preterm infants at discharge and within the first year after discharge. However, there is limited data on NHD in preterm neonates during neonatal intensive care unit (NICU) stay. Aim: To acquire quantitative data on head shapes among preterm neonates during NICU hospital stay. Study design: Investigators performed weekly head measurements on 68 premature infants starting within two weeks of birth or when medically stable until discharge. Infants recruited for the study were born at <34 weeks gestational age. Outcome measures: Cranial index (CI) and cranial vault asymmetry index (CVAI) were calculated from Ballert cranial caliper measurements during the infants stay (27 to 40 weeks postmenstrual age) in the NICU/Special Care Nursery (SCN) setting. Inter-rater retest reliability was determined for CI and CVAI. Results: Throughout the measurement period, CI consistently demonstrated dolichocephaly (CI < 0.76), and CVAI fluctuated above and below the range indicating plagiocephaly (CVAI ≥ 3.5%). Good to acceptable levels of test-retest reliability was demonstrated; prevalence of dolichocephaly and plagiocephaly at discharge was 82% and 36%, respectively; and mean head dimension measurement time for different combinations of bed types and support systems ranged from 1.1 to 1.9 min. Conclusions: Following the progression of CI and CVAI during the NICU stay using the cranial caliper method is reliable, and a substantial presence of NHD was reported. Highlights: Presence of nonsynostotic head deformities (NHD) can be assessed during neonatal intensive care unit (NICU) stay. This cohort consistently demonstrated dolichocephaly through NICU stay. Plagiocephaly was inconsistent but present in 1/3 of infants at any time. Following NHD progression is feasible using cranial calipers during NICU stay. NHD assessment prior to dismissal may aid in preventing and treating NHD.